THE STATUS, PROCEDURE AND IMPLEMENTATION OF INTERNATIONAL CONVENTIONS IN THE OMANI CONSTITUTION AND LEGISLATION - Fahad Al Aghbari; Muhamad Sayuti Hassan; Norfadhilah Mohamad Ali; Nurhafilah Musa; Nizar Qeshta; Salim Al Musalhi (Al-Risalah, 2026)
The Basic Statute of the State in the Sultanate of Oman grants ratified international conventions the force of law and outlines the procedures that the government and Parliament must follow before joining these treaties. However, Omani legislation varies in its treatment of international conventions. This study explores four scenarios in which these conventions interact with domestic legal frameworks. First, a convention may override the Constitution. Oman was a party to it before the Constitution’s enactment. Second, an international convention may take precedence over domestic laws when explicitly referenced. Third, national laws may prevail over conventions through explicit legislative decrees. Fourth, both international conventions and domestic laws may hold equal legal weight, raising questions about which authority prevails in cases of conflict. This study employs a Comparative legal analysis to examine the hierarchical relationship between international conventions and domestic legislation in  Oman. It investigates the challenges faced when  Parliament reviews international conventions, including their constitutional alignment, legal impact, and judicial applicability. The research highlights strengths and weaknesses in Oman’s legislative approach to international agreements and identifies gaps in the procedures leading to their ratification. The findings emphasise the need for a clear legal framework defining the supremacy of international conventions in Omani law. The study underscores the importance of aligning national bylaws with ratified international agreements and calls for explicit judicial criteria to resolve conflicts between domestic and international legal provisions. Furthermore, it stresses the need to enhance Parliament’s role in treaty evaluation to ensure consistency with constitutional and legal principles.